Bridging Academia and Industry: Talent Cultivation in Vocational Hotel Management via School-Enterprise Cooperation - Lv, Fanyang (Journal of Educational Research and Policies, 2026)
This paper investigates the application of the school-enterprise cooperation model within the hotel management program in vocational education. It analyzes the significance of this model for cultivating industry-ready talents in the hospitality sector and its contribution to the sustainable development of the hotel management discipline in vocational education contexts. The study proposes that optimizing talent cultivation requires the establishment of a long-term school-enterprise collaboration mechanism, refinement of the curriculum system, enhancement of both industry-specific competencies and pedagogical skills among teaching staff, and the development of comprehensive evaluation and feedback mechanisms. These measures aim to bridge the gap between academic training and industry demands, thereby improving the quality and relevance of hotel management education.